Forging peace in Damascus: On international aid, localized elite bargaining, and insider mediators - Merve Kania (Journal of Illicit Economies and Development (JIED), 2020)
Scholarship identified the present and future of war as increasingly characterized by urbanization and political-economic actors that Western international assistance defines as "illicit", "illiberal" or "criminal". This article asks how Western international assistance could and should shape war-to-peace transitions for contributing to the emergence of lasting non-violent "peaces". It combines scholarly insights from "pragmatic peacebuilding" scholarship and practice with interviews and grey literature on masterplanning projects in two neighborhoods in Damascus, Syria, that are prepared for "reconstruction" or "redevelopment", namely Qaboun and Basateen al-Razi. Thereby, it, on the one hand, challenges current approaches that, as in the case of Syria, presume that macropolitical pressure, diplomacy, and sanctions would forge an enduring outcome. It argues that "peace" must be recognized as an order that is particular to a given time, space, and their inherent relations of political-economic actors (political settlements) and is, thus, changeable and expandable to including more people's interests and subject matters. On the other hand, it promotes an elongation and bridging of the emerging consensuses across the reviewed literatures that supporting local actors who are recognized and respected as mediators by all relevant conflict parties provide for a fruitful avenue to expanding the inclusivity of peaces and their underlying political settlements. This adds to the repertoire of newly emerging sustainable peacebuilding methods and signposts towards further studies of "localized elite bargaining".
Keywords: 330; elite bargain; insider mediation; peace; post-war; Syria; urban